The Effect of Longpass Training Using Targets on The Accuracy of Long Passes in Soccer Sport Assist Soccer School Bekasi City - Tri Samsul Hadi; Azi Faiz Ridlo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the effect of longpass training using targets on the accuracy of long passes in soccer sports ssb assist soccer school Bekasi city. The research method used is an experimental approach with a one-group pre-test and post-test design. This study involved 20 players from Assist Soccer School Bekasi City. Data was collected through long pass accuracy tests before (pre-test) and after (post-test) long pass training using targets. The average pre-test score was 5.2, while the average post-test score increased to 7.4. This increase indicates an improvement in long pass accuracy after the training.  Soccer coaches are advised to integrate long pass training with targets in routine training sessions to improve players’ passing accuracy. Further research can be conducted involving larger samples and age variations to generalize these findings. The use of technology, such as video analysis, can help in providing more detailed feedback to players regarding their long pass technique.